The End of Municipal Street Railways in Detroit - Moore, Charles (Quarterly Journal of Economics, 1899)
Journal Article The End of Municipal Street Railways in Detroit Get access Charles Moore Charles Moore Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 14, Issue 1, November 1899, Page 121, https://doi.org/10.2307/1882358 Published: 01 November 1899